Evaluation of growth and meat performance of Pangasianodon hypopthalmus which fed with Cinnamomum burmanni leaves enriched diet - Setiawati, Mia; Sakinah, Aliyah; Jusadi, Dedi (Jurnal Akuakultur Indonesia, 2015)
ABSTRACT This research was performed to evaluate growth performance and meat quality at different feeding period of striped catfish Pangasianodon hypopthalmus fed on cinnamon leaves Cinnamomum burmanni enriched diet. Twenty fishes at the average body weight of 21.24±2.39 g were distributed  into 100×40×50 cm3 of aquarium. Fish were fed on the diet contained C. burmanni leaves of either 0.0%, 0.5%, 1.0%, or 1.5% respectively for 60 days. Fish were fed on those diets three times a day at satiation. Fish meat quality was evaluated by organoleptic test and proximate analysis at day-20, 40, and  60. The result showed that until day-40, fish fed on the diet contained 0.0%, 0.5%, and 1.0% cinnamon leaves had no significant difference on growth, hence still showed higher growth than fish fed at the dose of 1,5%. Meanwhile at day-60, fish fed on the diets contained either 0.5%, 1.0%, and 1.5% cinnamon leaves significantly had lower growth than that fed on 0.0% cinnamon leaves. In accordance to the growth response, diet contained 0.5% cinnamon leaves given for 40 days has shown the best texture and the highest protein content of fish meat.               Keywords: cinnamon leaves, striped catfish, growth, meat texture  ABSTRAK Penelitian ini dilakukan untuk mengevaluasi pertumbuhan dan kualitas daging ikan patin Pangasianodon hypopthalmus yang diberi pakan mengandung tepung daun kayu manis Cinnamomum burmanni dengan dosis berbeda. Sebanyak 20 ekor ikan patin berukuran 21,24±2,39 g dipelihara dalam akuarium berukuran 100×40×50 cm3. Ikan diberi empat jenis pakan yang mengandung daun kayu manis masing-masing sebesar 0,0%, 0,5%, 1,0%, dan 1,5% selama 60 hari. Pemberian pakan dilakukan sebanyak tiga kali sehari secara at satiation. Kualitas daging ikan diuji melalui uji organoleptik dan analisis proksimat pada hari ke-20, 40, dan 60. Hasil menunjukkan bahwa sampai hari ke-40 pemeliharaan, pertumbuhan ikan yang diberi pakan mengandung 0,0%, 0,5%, dan 1,5% daun kayu manis menunjukkan kinerja pertumbuhan yang tidak berbeda nyata, tetapi bernilai lebih tinggi daripada ikan yang diberi  dosis 1,5%. Berbeda halnya dengan kinerja pertumbuhan ikan pada hari ke-60, ikan yang diberi pakan 0,5%, 1,0%, dan 1,5% secara signifikan memiliki pertumbuhan yang lebih rendah dari ikan yang diberi pakan 0,0%. Sesuai dengan respons pertumbuhan, ikan yang diberi pakan 0,5% daun kayu manis selama 40 hari memiliki tekstur daging yang terbaik dan protein tertinggi. Kata kunci: daun kayu manis, ikan patin, pertumbuhan, tekstur